2015
DOI: 10.1038/cddis.2015.139
|View full text |Cite
|
Sign up to set email alerts
|

Dual induction of apoptotic and autophagic cell death by targeting survivin in head neck squamous cell carcinoma

Abstract: Survivin is ubiquitously expressed in patients with head neck squamous cell carcinoma (HNSCC) and is associated with poor survival and chemotherapy resistance. Sepantronium bromide (YM155) is a selective survivin suppressant that exhibits potent antitumor activities by inducing apoptosis and autophagy in various types of cancer. However, the curative effects and underlying mechanisms of YM155 in HNSCC remain unclear. This study showed that survivin overexpression positively correlated with p-S6, p-Rb and LAMP2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
52
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 50 publications
3
52
0
1
Order By: Relevance
“…This small imidazolium compound was initially identified from a pharmacological screen based on BIRC5 promoter inhibition and described as a first in class "Survivin suppressant". YM155 has been demonstrated to exert antitumor activity, to suppress Survivin expression and to induce tumor cell apoptosis and inhibit cell metastasis, in various human cancer models [13,14,[16][17][18]. Our current data show that YM155 not only inhibits cell growth but also induces apoptotic cell death of survivin-rich expressed SCC9 cells, a finding similar to those observed in Melanoma [25], renal Cell Carcinoma [26], multiple myeloma [27] and head neck squamous cell carcinoma [28,29].…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…This small imidazolium compound was initially identified from a pharmacological screen based on BIRC5 promoter inhibition and described as a first in class "Survivin suppressant". YM155 has been demonstrated to exert antitumor activity, to suppress Survivin expression and to induce tumor cell apoptosis and inhibit cell metastasis, in various human cancer models [13,14,[16][17][18]. Our current data show that YM155 not only inhibits cell growth but also induces apoptotic cell death of survivin-rich expressed SCC9 cells, a finding similar to those observed in Melanoma [25], renal Cell Carcinoma [26], multiple myeloma [27] and head neck squamous cell carcinoma [28,29].…”
Section: Discussionsupporting
confidence: 75%
“…YM155 has been demonstrated to exert antitumor activity, to suppress Survivin expression and to induce tumor cell apoptosis and inhibit cell metastasis, in various human cancer models [13,14,[16][17][18]. Our current data show that YM155 not only inhibits cell growth but also induces apoptotic cell death of survivin-rich expressed SCC9 cells, a finding similar to those observed in Melanoma [25], renal Cell Carcinoma [26], multiple myeloma [27] and head neck squamous cell carcinoma [28,29]. However, YM155 treatment did not affect growth and apoptosis of poor-survivin expressed SCC25 cells, suggesting YM155 could be a target for the treatment of survivin-rich expressed OSSC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13,30 YM155, a potent survivin inhibitor, has been used as an anti-cancer agent in many tumors, 9 which can suppress the proliferation of the tumor cells and induce tumor cells death. [31][32][33] We examined that YM155 significantly inhibited the proliferation ability of OSCC cell lines in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12] In OSCC, YM155 can suppress its growth by promoting apoptosis and autophagy and inhibiting proliferation. 13,14 Rapamycin, an immunosuppressive agent, was used widely to avoid immunological rejection in the organ transplantation. 15,16 Recently, it was revealed that rapamycin could suppress tumor growth through anti-angiogenesis and promote cell death by inhibiting the mammalian target of rapamycin (mTOR) pathway.…”
Section: Introductionmentioning
confidence: 99%